Risk factors associated with development of congestive heart failure among hypertensive patients attending selected health facilities in Kiambu County, Kenya - Mugo, Onesmus; Osero, Justus O. S.; Chomi, Eunice; Muiruri, Mary G.; Kamau, Peter (International Journal Of Community Medicine And Public Health, 2021)
Background: The study objective was to determine prevalence of congestive heart failure among hypertensive patients attending selected health facilities in Kiambu County, Kenya so as to determine the disease burden in the region. Methods: This investigation carried out between 1 August to 31 August 2020 applied a cross sectional study design with both quantative and qualitative approaches. The study employed a variety of sampling approaches to pick the health care facilities where the research was conducted. The sample population was patients seen in the medical outpatient clinic every week and key informants. The inclusion criteria were hypertensive patients attending the MOPC in PCEA Kikuyu hospital and in Thika level 5 hospital and that gave informed consent excluding all critically ill hypertensive subjects and those that had mental disorders. A sample size of 239 study subjects was arrived at. Using questionnaires and key informant interviews, data was obtained. The researchers acquired informed consent from the research participants. The interview took place in two rooms within the medical outpatient clinic facilities where privacy and confidentiality were upheld. Quantitative data was analysed using means, percentages standard deviation to summarize the data especially in helping the researcher know the prevalence of congestive heart failure among the hypertensive patients seen. Qualitative data was analysed by identifying patterns after data collection. Results: The prevalence of congestive heart failure among hypertension individuals attending selected health facilities in Kiambu County was 9.6% with body mass index, activity level and sedentary lifestyle being associated with development of congestive heart failure. Conclusions: The prevalence of congestive heart failure is significant with studied modifiable risk factors contributing to congestive heart failure development recommending that the Kiambu County government to investigate ways of lowering the prevalence and addressing the modifiable risk factors.